The strategic use of the past and future in organizational change - Carroll, Craig E. (Journal of organizational change management ;, 2002)
The strategic use of the past and future in organizational changeWho controls the past ... controls the future: who controls the present controls the past(George Orwell, 1984). This issue is a milestone for the study of organizational history - an emergingfield that crosses intellectual domains and continents.